Návrh podnikatelského záměru na založení hotelu s minipivovarem - Hetmánková, Gabriela (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Bakalářská práce se zaměřuje na vypracování návrhu podnikatelského záměru na založení hotelu s minipivovarem ve městě Zlín. Popisuje postup řešení, skladbu podnikatelského záměru a obsah jednotlivých jeho částí včetně analýzy prostředí, trhu a rizik.

The bachelor thesis focuses on creating a Business plan proposal for establishment of the hotel with a microbrewery in the city of Zlin. It describes the solving procedure, structure of business plan and the content of it´s individual parts, including the analysis of the environment, market and risks.
Business Plan Proposal for the Establishment of the Hotel with a Microbrewery
Keywords: Společnost; podnikatelský záměr; finanční plán; marketingový plán; analýza; riziko; podnikání; podnikatel; hromadné ubytovací zařízení.; Company; business plan; financial plan; marketing plan; analysis; risk; business; businessman; collective accommodation facility.